Sosialisasi Penyalah Gunaan Narkoba Pesantren Sebagai Benteng Terakhir Mencegah Peredaran Narkoba Di Pesantren Al-MuhajirinDusun Sumberwuluh Desa Lakardowo Kecamatan Jetis Kabupaten Mojokerto Propinsi Jawa Timur - Jaka Prima; Putut Hadi Suprayitno; Dedy Muharman; Hascaria Budi Prasetya; Andri Novianto; Junus Junus (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
This service was carried out to remind the role of Islamic Boarding Schools as the last bastion in preventing drug trafficking in the community, where the phenomenon of drug trafficking has become a serious problem in various layers of society, so that Islamic Boarding Schools, as Islamic educational institutions that have the potential to contribute to prevention efforts. The methodology of this service was carried out by means of lectures conveying material on the understanding and dangers of drugs / drugs and how to prevent their circulation. In addition, discussions were also held by means of questions and answers and the delivery of the importance of the role of santri and satriwati to understand how Islamic Boarding Schools can implement anti-drug programs, as well as the impact on the behavior of students. The results of this research are expected to provide a deeper insight into the effectiveness of the role of Islamic boarding schools in combating drug trafficking in the community. In a broader context, this dedication has important implications in the development of drug prevention strategies in Indonesia. The results of this research can also be the basis for policy improvement and cooperation between religious educational institutions and the government in addressing the drug problem. Thus, this research is expected to make a positive contribution in the effort to protect the community from the threat of drug trafficking